2021
DOI: 10.3389/fmed.2021.640814
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Fat: A Cardiovascular Risk Factor With Implications in Chronic Kidney Disease

Abstract: There is a growing interest in the potential role of adipose tissues in cardiac and renal pathophysiology, and determining the mechanisms by which fat compartments around the heart and kidneys influence cardiovascular disease is of clinical importance in both general and high-risk populations. Epicardial fat and perirenal fat have been associated with adverse outcomes in chronic kidney disease (CKD) patients. Epicardial fat is a rich source of free fatty acids and is capable of secreting inflammatory and pro-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Fatty kidney comprises perirenal, sinus, and renal parenchyma fat [166][167][168][169]. Perirenal and sinus fat volumes can be measured with a variety of high-resolution MRI techniques to visualize the renal facia that separate perirenal fat from the pararenal depot.…”
Section: Fatty Kidneymentioning
confidence: 99%
“…Fatty kidney comprises perirenal, sinus, and renal parenchyma fat [166][167][168][169]. Perirenal and sinus fat volumes can be measured with a variety of high-resolution MRI techniques to visualize the renal facia that separate perirenal fat from the pararenal depot.…”
Section: Fatty Kidneymentioning
confidence: 99%
“…Studies have associated EAT volume with unfavourable clinical outcomes in chronic kidney disease (CKD) [ 64 , 65 ]. Interestingly, analogously to the way that EAT is an organ-specific adipose tissue impacting the heart, there is growing evidence that the perirenal adipose tissue (PF) has a significant impact on renal pathophysiology [ 66 ]. It was demonstrated that PF is an independent predictor for CKD progression and is associated with cardiorenal dysfunction [ 67 ].…”
Section: Section 1: Physiological and Anatomical Features Of Eatmentioning
confidence: 99%
“…Epicardial fat accumulation has been linked to poor consequences including albuminuria, decline in eGFR, atherosclerosis and worse prognosis in CKD patients. [108][109][110][111] Exact physiological role of epicardial fat accumulation is currently unclear; nevertheless, it is involved in the secretion of many cytokines such as leptin, adiponectin, resistin, omentin and others. Under physiological conditions, the balance of these cytokines supports anti-inflammatory and anti-atherogenic effects while excess accumulation of epicardial fat accumulation leads to contradictory outcomes like fat accumulation in many other tissues including liver, kidney and subcutaneous tissues.…”
Section: And Cardiovascular Diseasementioning
confidence: 99%
“…Another important issue to be addressed is the potential effects of fat accumulation in other tissues including epicardium on cardio‐renal outcomes. Epicardial fat accumulation has been linked to poor consequences including albuminuria, decline in eGFR, atherosclerosis and worse prognosis in CKD patients 108–111 . Exact physiological role of epicardial fat accumulation is currently unclear; nevertheless, it is involved in the secretion of many cytokines such as leptin, adiponectin, resistin, omentin and others.…”
Section: Fatty Kidney and Kidney And Cardiovascular Diseasementioning
confidence: 99%